Low-dose ionising radiation effects: effects of thoron inhalation. (1st January 2014) - Menon, Aditya; Indu, R.; Chacko, Tiju; Nair, Cherupally Krishnan Krishnan
Cellular DNA damage, tissue antioxidant levels, serum parameters, blood count and histopathological alterations were examined in tissues of mice exposed to thoron (average radiation dose0.065 μSv/hr). Alkaline cometassay results indicated that inhalation of thoron caused significant increase in the damage to DNA of lung tissue, while there was no significant damage to DNA in bone marrow cells. A small increase in cellular DNA damage was also seen in blood leukocytesfollowing thoron exposure. Inhalation of thoron induced severe damage in the lung cells leading to their elimination by apoptosis. Histology of lungs showed areas of abnormalities. An increase in the level of inflammatory response mediator, NF-κB, was also observed in the lung tissue of exposed mice. The DNA damage in lung cells could be induced by high energy radiation emanating from radioactive decay of thoron and its progeny particularly the alpha radiation of 8.88 MeV from 212 Po.